Feasibility Study of Graphics Rendering in Cloud - Kah Meng, Tan (Universiti Teknologi Petronas, 2011)
A locally rendered graphics is restricted by the local CPU and GPU capability. However, distributing rendering process across multiple CPUs will reduce rendering time. Map Reduce framework is originally developed by Google for the ease of web search applications on a large numbers of CPUs. With the application of cloud project, a MapReduce framework, graphics rendering is distributed across multiple CPU. In this research, the author studies the feasibility of using MapReduce framework on multiple CPUs to render graphics. The author even developed an interface to facilitate the display of graphics rendering in multiple frames.